2015
DOI: 10.1021/es5061726
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Aromatics Content in Gasoline on Gaseous and Particulate Matter Emissions from SI-PFI and SIDI Vehicles

Abstract: We assessed the emissions response of a fleet of seven light-duty gasoline vehicles for gasoline fuel aromatic content while operating over the LA92 driving cycle. The test fleet consisted of model year 2012 vehicles equipped with spark-ignition (SI) and either port fuel injection (PFI) or direct injection (DI) technology. Three gasoline fuels were blended to meet a range of total aromatics targets (15%, 25%, and 35% by volume) while holding other fuel properties relatively constant within specified ranges, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 48 publications
10
61
0
1
Order By: Relevance
“…Significant differences in the EFs among different gas-and particle-phase species were observed. For example, the EFs of primary PM in both number and mass concentration using F3 fuel were only 20 % larger than those using F2 fuel, consistent with previous studies (EPA, 2013;Karavalakis et al, 2015). Similar results were also obtained for most of the alkane VOCs as well as NO.…”
Section: Aromatic Emission and Soa Productionsupporting
confidence: 90%
See 1 more Smart Citation
“…Significant differences in the EFs among different gas-and particle-phase species were observed. For example, the EFs of primary PM in both number and mass concentration using F3 fuel were only 20 % larger than those using F2 fuel, consistent with previous studies (EPA, 2013;Karavalakis et al, 2015). Similar results were also obtained for most of the alkane VOCs as well as NO.…”
Section: Aromatic Emission and Soa Productionsupporting
confidence: 90%
“…Therefore, the higher emission of aromatic VOCs will likely result in more SOA formation potential. Existing fuel-effect experimental and model studies have shown that high-aromatic fuel in gasoline fuel will lead to more emissions of primary PM as well as some aromatic VOCs (Zervas et al, 1999;EPA, 2013;Karavalakis et al, 2015;Wang et al, 2016), indicating the considerable potential impact of gasoline aromatic content on SOA production. Furthermore, though aromatic content in diesel fuel may have an insignificant impact on SOA formation (Gordon et al, 2014b), SOA production from gasoline vehicle is considered more sensitive to aromatic content than that from diesel vehicle (Jathar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…GDI technology enables both an increase in specific power and a better fuel economy (with simultaneous reduction in CO 2 emissions), compared to traditional port fuel injection (PFI) engines (Alkidas, 2007). However, GDI engines are known to produce higher PM mass, black carbon, and particle number emissions than PFI engines and modern technology diesel engines equipped with diesel particulate filters (DPFs) (Karavalakis et al, 2015;Saliba et al, 2017;Zinola et al, 2016). PM formation in GDI engines is due to partially evaporated liquid fuel leading to fuel rich regions in the combustion chamber that promote the generation of PM (Karlsson and Heywood, 2001;Piock et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A companion paper to this study presents the criteria pollutant and air toxic emissions associated with this study. 24 …”
Section: â–  Introductionmentioning
confidence: 99%